2016
DOI: 10.1194/jlr.m064980
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of a lipoxygenase from Cyanothece sp. may reveal novel features for substrate acquisition

Abstract: This article is available online at http://www.jlr.org PUFA oxygenation is a process that leads to the formation of bioactive lipid compounds with a diversity of biological functions in plants and animals ( 1, 2 ). Oxidation of PUFAs may be catalyzed by two major classes of enzymes, cyclooxygenases or ␣ -dioxygenases and lipoxygenases (LOXs) ( 3 ). Of the two, LOXs are nonheme iron-containing dioxygenases that are widely found in higher plants and animals, but have also been detected in some corals, mosses, fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 55 publications
(67 reference statements)
0
31
0
Order By: Relevance
“…The coordinating sphere is similar to coral 8R-LOX, but the metal ligands do not superimpose as neatly as those of coral 8R-LOX, sLOX-1, and 15S-LOX of P. aeruginosa (Fig. 3B) (2,16,19,20). The distances between the coordinating residues, manganese, and water are indicated in Table 2 along with a comparison with three FeLOX.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinating sphere is similar to coral 8R-LOX, but the metal ligands do not superimpose as neatly as those of coral 8R-LOX, sLOX-1, and 15S-LOX of P. aeruginosa (Fig. 3B) (2,16,19,20). The distances between the coordinating residues, manganese, and water are indicated in Table 2 along with a comparison with three FeLOX.…”
Section: Resultsmentioning
confidence: 99%
“…These are four structures of soybean LOX (sLOX-1, LOX-3, VLX-B, and VLX-D) (9 -13), three human LOX (15-LOX-2, 12S-LOX, and 5-LOX) (2,13,14), coral 8R-LOX and 11R-LOX (15,16), rabbit arachidonate 15-LOX-1 (17), porcine 12S-LOX (18), 15S-LOX of Pseudomonas aeruginosa (19), and linoleate 9R-LOX of Cyanotheca sp. (20). Plant and mammalian LOX consist of two domains, a relatively small eight-stranded ␤-barrel domain with homology to the PLAT (polycystin-1, lipoxygenase, ␣-toxin) domain and a larger catalytic domain of ␣-helices containing the substratebinding channel and the catalytic iron (2).…”
mentioning
confidence: 99%
“…6). Analysis of the products revealed that the positional specificities were the same as for linoleic acid, as FoxLOX, which is characterized as 13-LOX [10], produced mainly 13-HPODE and the 9-LOX CspLOX1 [19] produced mainly 9-HPODE (Fig. As it might be possible, that other LOX also produce 11-HPODE under these optimized conditions, we analyzed LOX from various phylogenetic groups for 11-HPODE formation using HPLC analysis.…”
Section: Formation Of 11-hpode and Isomerization Of 11-hpode By Othermentioning
confidence: 99%
“…When following the reaction of CspLOX2 at 234 nm with a spectrophotometer, two characteristic features distinguish the CspLOX2 reaction from most other LOX reactions. [19] has a comparably long lag phase (Fig. Second, the reaction comprises two linear phases, a first steep increase of absorbance and a following flat increase (Fig.…”
Section: -Hpode Is Only Transiently Formedmentioning
confidence: 99%
“…Amino acid sequences with homology to zonadhesin occur in peptidases and few other proteins of P. pastoris. 6 Adhesion molecules of bacteria and fungi are crucial for cell-cell interaction, adherence to surrounding tissues, and the virulence of pathogens (34). Zonadhesin and several other fungal adhesins contain a ligand binding N-terminal domain of 300 residues and a C-terminal domain with repeats of Thr, Ser, and hydrophobic residues (34,35).…”
Section: Discussionmentioning
confidence: 99%